What CATIE Found: Results From the Schizophrenia Trial - Swartz, Marvin S. (Psychiatr Serv, 2008)
The authors provide an overview of the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) sponsored by the National Institute of Mental Health. CATIE was designed to compare a proxy first-generation antipsychotic, perphenazine, to several newer drugs. In phase 1 of the trial, consenting patients were randomly assigned to receive olanzapine, perphenazine, quetiapine, risperidone, or ziprasidone for up to 18 months on a double-blind basis. Patients with tardive dyskinesia were excluded from being randomly assigned to perphenazine and were assigned to one of the four second-generation antipsychotics in phase 1A. Clozapine was included in phase 2 of the study. Overall, olanzapine had the longest time to discontinuation in phase 1, but it was associated with significant weight and metabolic concerns. Perphenazine was not significantly different in overall effectiveness, compared with quetiapine, risperidone, and ziprasidone. Also, perphenazine was found to be the most cost-effective drug. Clozapine was confirmed as the most effective drug for individuals with a poor symptom response to previous antipsychotic drug trials, although clozapine was also associated with troublesome adverse effects. There were no differences in neurocognitive or psychosocial functioning in response to medications. Subsequent randomizations suggest that a poor response to an initial medication may mean that a different medication will be more effective or better tolerated. Although the CATIE results are controversial, they are broadly consistent with most previous antipsychotic drug trials and meta-analyses; however, the results may not generalize well to patients at high risk of tardive dyskinesia. Patient characteristics and clinical circumstances affected drug effectiveness; these patient factors are important in making treatment choices.